2021
DOI: 10.3390/genes12050624
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Microcoria: Clinical Features and Molecular Genetics

Abstract: Iris integrity is required to regulate both the amount of light reaching the retina and intraocular pressure (IOP), with elevated IOP being a major risk factor for glaucoma. Congenital microcoria (MCOR) is an extremely rare, autosomal dominant disease affecting iris development and hindering both of these functions. It is characterized by absent or underdeveloped dilator muscle fibers and immaturity of the iridocorneal angle—where the aqueous humor is drained—which play a central role in IOP regulation. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 59 publications
1
26
2
Order By: Relevance
“…8 Previous literature has majorly reported "microdeletions" in the 13q32 region causing congenital microcoria. 9 Multiple families of this rare disease were reported, with submicroscopic chromosomal rearrangements mapped on the locus at 13q32. It was concluded that the GPR180 gene, located within the deleted region, encodes a G protein-coupled receptor involved in smooth muscle cells growth and it was concluded that deletions of this gene are the cause of MCOR.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous literature has majorly reported "microdeletions" in the 13q32 region causing congenital microcoria. 9 Multiple families of this rare disease were reported, with submicroscopic chromosomal rearrangements mapped on the locus at 13q32. It was concluded that the GPR180 gene, located within the deleted region, encodes a G protein-coupled receptor involved in smooth muscle cells growth and it was concluded that deletions of this gene are the cause of MCOR.…”
Section: Discussionmentioning
confidence: 99%
“…The iris is composed of four layers: anterior border layer, stroma and sphincter muscle, anterior pigment epithelium layer and dilator muscle, and posterior pigment epithelium layer. Among them, the sphincter muscle can constrict the pupil in miosis and dilator muscle can expand the pupillary aperture in mydriasis to control the quantity of light to enter the eye [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The definition of congenital microcoria was first described by Holth in 1923 [ 6 ]. Congenital microcoria manifested in pinhole pupil (< 2 mm), poor development of the crypt and collarette, thinning iris stroma with corresponding transillumination, abnormal iridocorneal angle with minimally pigmented [ 4 , 7 ]. Congenital microcoria is associated with axial myopia, glaucoma, astigmatism, cataract and goniodysgenesis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the physical characteristics of the eye and medical information about it provide the researcher with a broad understanding of the iris as shown in figure 4 (Bhanu & Kumar, n.d.). The iris is composed of two main regions (Angée et al, 2021):…”
Section: Human and Computer Visionmentioning
confidence: 99%